Battling the Prince : a Woman Fights for Democracy. - Snyder-Hall, Claire (State University of New York Press, 2021)
"What happens when a democratic theory professor gets involved with the Democratic Party? In this political memoir, Claire Snyder-Hall shares lessons learned from eight years in party politics. She tells the story of organizing a grassroots campaign for state senate in a district dominated by good ole boys, of a political milieu in which a letter to the editor results in a smear campaign and broken friendships, and of battling a party establishment more concerned about shoring up its own power than engaging everyday people or fighting for their needs. Using an intersectional understanding of identity, Snyder-Hall unpacks the ways in which gender, class, and sexuality affect political campaigns, and offers advice for progressives. She also draws on insights from Machiavelli, Rousseau, Marx, and Gramsci to argue that a democratic republic requires a politically engaged populace, a democratic culture, and economic justice, and this can only be achieved when people defend democratic values in the face of rising authoritarianism, stand up to bullies, transform their political consciousness, and a create a party willing to fight for the 99%." -- Back cover.
Keywords: Snyder-Hall, Claire.; Democratic Party (U.S.) -- History -- 21st century.; Democratic Socialists of America -- History -- 21st century.; Democratic Socialists of America; Democratic Party (U.S.); Women political activists -- New York (State) -- New York -- Biography.; Women political activists -- United States -- Biography.; Political activists -- United States -- Biography.; Feminists -- United States -- Biography.; Liberals -- United States -- Biography.; Lesbians -- United States -- Biography.; Women politicians -- United States -- Biography.; United States -- Politics and government -- 21st century.; Democracy -- United States -- History -- 21st century.; Progressivism (United States politics); Right and left (Political science) -- United States -- History -- 21st century.; Women and democracy -- United States -- History -- 21st century.; Political parties -- United States -- History -- 21st century.; Femmes activistes -- New York (État) -- New York -- Biographies.; Femmes activistes -- États-Unis -- Biographies.; Activistes -- États-Unis -- Biographies.; Féministes -- États-Unis -- Biographies.; Libéraux (Science politique) -- États-Unis -- Biographies.; Lesbiennes -- États-Unis -- Biographies.; Femmes politiques -- États-Unis -- Biographies.; États-Unis -- Politique et gouvernement -- 21e siècle.; Progressisme -- États-Unis.; Femmes et démocratie -- États-Unis -- Histoire -- 21e siècle.; BIOGRAPHY & AUTOBIOGRAPHY / Political.; Women politicians; Women and democracy; Right and left (Political science); Politics and government; Political parties; Political activists; Liberals; Lesbians; Feminists; Democracy; Women political activists; United States; New York (State) -- New York; 2000-2099; UNITED STATES; POLITICAL SCIENCE; Electronic books.; History; Biographies